The Effect of Picture Series on Students' Reading Comprehension of The Eighth Grade Students at UPTD SMP Negeri 3 Pematangsiantar - Pardede, Ros Meylani Putri; Rohana Sinaga, Asima; Maria Efipanias Manihuruk, Leonita; Anggita Ristia Damanik, Bernieke (Innovative: Journal Of Social Science Research, 2024)
This research aimed to assess the effect of Picture Series on reading comprehension among eighth-grade students at UPTD SMP Negeri 3 Pematangsiantar, based on the theory by King and Stainley. A quantitative methodology was employed, focusing on the eighth-grade population for the academic year 2024/2025. The sample consisted of two classes: VIII-5 as the experimental group, which included 31 students taught using Picture Series, and VIII-6 as the control group, also with 31 students, who were taught using the Monothone strategy. Data were collected through pre-tests and post-tests. The experimental group had a mean pre-test score of 66.93, which increased to 82.74 in the post-test, while the control group improved from 63.70 to 72.09. The t-test result was 4.535, exceeding the t-table value of 1.671 at a 5% significance level. This led to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho), indicating that Picture Series significantly enhances reading comprehension among eighth-grade students at UPTD SMP Negeri 3 Pematangsiantar.